PERAN ASEAN DEFENCE MINISTERS MEETING PLUS (ADMM PLUS) SEBAGAI FORUM DIPLOMASI PERTAHANAN DI KAWASAN ASIA - M. Harviend Gilang P (Jurnal Studi Diplomasi dan Keamanan, 2016)
The ADMM-Plus is a forum for ASEAN and its eight Dialogue Partners to strengthen security and defence cooperation for peace, stability, and development in the region. The initial ADMM-Plus was convened in Ha Noi, Viet Nam, in 2010. The Defence Ministers then agreed on five areas of practical cooperation to pursue under this new mechanism, namelymaritime security, counter-terrorism, humanitarian assistance and disaster relief, peacekeeping operations and military medicine. To facilitate cooperation on these areas,Experts' Working Groups (EWGs) are established.  This paper aims to describe the role of ADMM Plus as an important platform for Asia’s defence diplomacy. It argues that, like other ASEAN offspring forums, the ADMM-Plus plays an important role in building confidencebuilding measures in the five priority areas. It is, however, still unclear whether it could lead to next steps of defence cooperation.